The Optical Properties of Sub-micrometer WS2 Preparing Using Electrochemical Fabrication - Fuad Pratama; Ismudiati Puri Handayani; Edy Wibowo (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
Photonic band gap tunability is crucial in designing optoelectronic devices. Nanostructure semiconductors with tunable band gaps which depend on the dimensionality, have become the potential candidate for tunable nano optoelectronic devices. However, it has a lot of challenges in their fabrication such as the limited number of homogenous particles and high-cost production. As an alternative, sub-micrometer particles with the order of hundred nanometers are more easily fabricated and exhibit tunable optoelectronic properties. In this study, sub-micrometer WS2 was fabricated using low-cost electrochemical methods. Two clusters of particles with the average size of 100 nm and 600 nm are observed. The number of sub-micrometer particles increases with the increasing of fabrication time. The photoluminescence spectra show wide peak centered around 800 nm suggesting the possible application in visible light emitting devices. The peak position varies with the time variation showing that the optical properties might be tuned during fabrication. This study points out that simple solution processed fabrication method can produce sub micrometer particles with tunable optical properties.